Nuclear ecologies: art and collaboration in post-3.11 Japan - Deichert, Theresa (Routledge, 2026)
This book traces the Fukushima nuclear disaster of March 2011 and how art emerged as a powerful response to the socio-political and environmental consequences. Artists turned to collaborative and ecological practices to make sense of the crisis, challenging official narratives and responding to the violence of radioactive contamination
"This book is a revised version of the doctoral dissertation "Nuclear Ecologies: Contemporary Japanese Art, (Non)human Collaborations and the 3.11 Disaster" submitted to Heidelberg University" - Editor's note
Dissertation eingereicht unter dem Titel: Nuclear ecologies : contemporary Japanese art, (non)human collaborations and the 3.11 disaster
Keywords: Hochschulschrift; Geschichte 2011-2025; Ökologie; Gesellschaft; Kunst; Kerntechnischer Unfall; Japan